1996
DOI: 10.1089/aid.1996.12.223
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Zidovudine Affectsin Vitroandin Vivothe Efficiency of Phosphorylation of Thymidine Kinase

Abstract: The purpose of this study was to investigate the mechanism of acquired cellular resistance to AZT, a mechanism that has been described as a potential source of drug resistance in addition to viral mutations. To study this phenomenon the kinetics parameters of thymidine kinase (TK) activity have been defined in CEMazt, a cell line previously selected for resistance to AZT, in comparison with the parental AZT-sensitive CEM cells. The results revealed that the value of the maximum velocity (Vmax) of TK activity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 21 publications
2
40
0
1
Order By: Relevance
“…3) on the concentrations of metabolites and found no effect for 4Ј-Ed4T and 3TC; however, there was a trend for moderation of the concentration of AZT metabolites by gender (P ϭ 0.17 for gender ⅐ metabolite concentration). When the trajectories of the analog concentrations from monophosphate to triphosphate were analyzed by gender Decreased expression of phosphorylating enzymes has been implicated in the observed resistance to nucleoside analogs (5,25). Thus, we investigated whether the variation in intracellular metabolite concentrations is associated with the activity and/or expression of the cellular kinases involved in the phosphorylation of nucleoside analogs (i.e., 4Ј-Ed4T, AZT, and 3TC).…”
Section: Resultsmentioning
confidence: 99%
“…3) on the concentrations of metabolites and found no effect for 4Ј-Ed4T and 3TC; however, there was a trend for moderation of the concentration of AZT metabolites by gender (P ϭ 0.17 for gender ⅐ metabolite concentration). When the trajectories of the analog concentrations from monophosphate to triphosphate were analyzed by gender Decreased expression of phosphorylating enzymes has been implicated in the observed resistance to nucleoside analogs (5,25). Thus, we investigated whether the variation in intracellular metabolite concentrations is associated with the activity and/or expression of the cellular kinases involved in the phosphorylation of nucleoside analogs (i.e., 4Ј-Ed4T, AZT, and 3TC).…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that decreased TK activity in lymphocytes from HIV-infected patients may be related to prolonged treatment with AZT (jacobsson et al, 1995;Antonelli et al, 1996). In resistant cell lines, prolonged incubation with AZT is also associated with decreased activity of AZT-activating kinases.…”
Section: Discussionmentioning
confidence: 99%
“…AZT was phosphorylated only in extracts from MOLT4/8 cells; no phosphorylation was observed in extracts from MOLT4/grAZT250 cells. AZTresistant CEM and jurkat cells showed a 100-to 1000-fold decrease in phosphorylation efficiency (Vrna/K rn) for thymidine; in both cell lines the K rn value for thymidine was significantly increased (Avramis et al, 1993;Antonelli et al, 1996). MOLT4/grAZT250 cells had an Tl-fold lower phosphorylation efficiency for thymidine than the parental cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radioisotopic labeling of the substrate of the enzyme revealed that TK1 enzymatic activity is decreased as well (unpublished data). Patients exposed for long term also present a decrease on the TK 1 enzyme activity [22,23]. Additionally, lack of expression of the active form of the enzyme has been seen in human mammary epithelial cells that do not incorporate AZT into the DNA (Olivero et al, TAAP, in press).…”
Section: Azt Is a Transplacental Carcinogen In Micementioning
confidence: 99%